Perspective—Potential Benefit of Li-Rich Cathode Materials: Reduction of Co and Ni Content Rather than Achievement of Ultra-High Capacities. Issue 5 (1st May 2022) - Benedek, Roy
Abstract : In the conventional cycling protocol for lithium and manganese rich NMC layered oxides (LMRNMC), the upper cutoff voltage V cut is extended to ∼ 4.8, to achieve capacities of ∼ 250 mAh g −1 . With this mode of operation, structural rearrangements result in voltage fade upon cycling. A strategy is proposed to avoid these structural rearrangements based on (a) restricting V cut to values < ∼4.6 to shut down the bulk instabilities, and (b) application of a (preferably) semi-coherent coating that protects the surface oxygen. The potential benefit of this strategy would be to minimize Co and Ni content, compared to Ni-rich NMC.